THE ORIGIN OF JOSEPHINITES: A NEW NOBLE GAS STUDY - Staudacher T.; Allègre C.J. (My University, 1990)
We performed a complete noble gas study on eight different josephinites and one oregonite. The 4He/3He ratios range between 100,000 and 330,000 and are probably due to a combination of a MORB He-component from the Josephinite Peridotite massif, where these nickel-iron specimens are found, and either atmospheric He or radiogenic He from the underlying continental or subcontinental basement. The 40Ar/36Ar ratios of 302 to 381 are slightly higher than the ratio of air-argon. The neon, krypton and xenon isotopic ratios are identical to the corresponding air ratios. We cannot confirm large3He and21Ne excesses published earlier. The observed noble gas isotopic signatures are in agreement with a formation of josephinites near the surface. The data do not favour a deep mantle origin or a formation at the mantle-core boundary as proposed before.